Study on Appropriateness of Prescribing Patterns in Geriatric Patients with Renal Failure at a Tertiary Care Teaching Hospital - Velu., Shivashankar; Harikrishnan S., Jaivy P. Joseph, Irene Vincent,Josy Elsa Eapen (International Journal of Innovative Research in Medical Science, 2016)
Since the beginning of the 20th century, the number of elderly people is steadily increasing. The effect of advancing age in decreasing renal reserve and the associated comorbid conditions of the elderly patients increase the risk for kidney injury. Patients with CKD require appropriate adjustment of nephrotoxic and renally cleared medications to ensure safe and effective pharmacotherapy. In particular, older patients are at a higher risk of developing advanced disease and related adverse events caused by age-related decline in renal function and the use of multiple medications to treat comorbid conditions and inappropriate dosing can cause toxicity or ineffective therapy. The objective of the study was to analyze the prescribing pattern of drugs in renally impaired patients, to identify the inappropriate drugs prescribed, do necessary dose adjustments and to evaluate drug interactions. A prospective interventional study was conducted. Data was collected from patient records during regular ward rounds. The collected data was analyzed thoroughly using Truven Health Micromedex Solutions software. The prevalence of renal failure in geriatric population was found to be 24%. Among the geriatric population, renal failure was found significantly more in males. The degree of renal impairment was assessed and the study population was categorized according to K/DOQI and was found that a majority falls in the ESRD category (48.33%). The required dosage adjustments were identified and rectified with proper interventions. It was found that 42.85% of drugs required dose reduction, 28.57% of drugs require dose increment and 28.57% of drugs were withdrawn. A total of 33.3% major interactions were found and diuretics were found to be involved in a majority of the interactions. The study signifies the importance of clinical pharmacists having an essential role to provide safe and effective therapy for patients with renal failure. The pharmacists need to identify the drugs requiring dosage adjustments and manage the drug interactions by resolving the same; can improve the safe and effective use of drugs in renal failure cases.